Structural change and the climate risk premium during the green transition - Sophie Lian Zhou; Frederick van der Ploeg (Deutsche Bundesbank, 2024)
We study climate change in a model with a carbon-intensive and a green sector, each subject to stochastic productivity shocks, and show how the underlying economic structure affects the risk-adjusted discount rate and the climate risk premium in the social cost of carbon (SCC). Consumption growth, aggregate consumption volatility, and the climate beta depend on the elasticity of substitution between the two sectors and the relative size of the sectors, and vary during the green transition. The time path of the climate risk premium is hump-shaped, with the climate beta playing a dominant role in its magnitude. For strong substitutability between the two sectors and low correlation between the sectoral shocks, decarbonization can temporarily reduce aggregate consumption risk, as the climate beta becomes negative in the mid phase of the transition. The risk-adjusted discount rate first falls then rises during the green transition, leading to a SCC to GDP ratio that rises then falls as the green sector grows. We illustrate our analytical results numerically.
Keywords: E60; G12; H23; O41; Q54; 330; social cost of carbon; climate beta; carbon risk premium; two-sector model; asset pricing